IKTIBAR JURNALISME WARGA BAGI KOMUNITAS WARIA DI YOGYAKARTA - Adhi, Irawan Sapto; Afriati, Dwiningsih; Sari, Ade Rakhma Novita; Cahya, Fikri Nur (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
This article aimed to describe citizen jurnalism has been used in the fight for civil and political rights. Then, describe the fulfillment civil and political rights of shemale in Yogyakarta. The results that citizen jurnalism can used as a tool in fight for civil and political rights. And the fulfillment civil rights of shemale is unfulfilled overall.